Recent Progress of Symmetrically Substituted 1,1´ -Binaphthyls for Asymmetric Catalytic Hydrogenation - Mei, Luo; Xiao Xuan, Li (Asian Journal of Chemistry, 2010)
In the present work, a review on recent progress of symmetrically substituted 1,1´-binaphthyls for asymmetric catalytic hydrogenation is presented.